Epitaxial graphene/Ge interfaces: a minireview. Issue 21 (27th May 2020) - Dedkov, Yuriy; Voloshina, Elena
Abstract : This review highlights recent progress in the studies of the growth and electronic properties of epitaxial graphene on Ge surfaces. Abstract : The recent discovery of the ability to perform direct epitaxial growth of graphene layers on semiconductor Ge surfaces led to a huge interest in this topic. One of the reasons for this interest is the chance to overcome several present-day drawbacks on the method of graphene integration in modern semiconductor technology. The other one is connected with the fundamental studies of the new graphene–semiconductor interfaces that might help with the deeper understanding of mechanisms, which governs graphene growth on different substrates as well as shedding light on the interaction of graphene with these substrates, whose range is now spread from metals to insulators. The present minireview gives a timely overview of the state-of-the-art field of studies of the graphene–Ge epitaxial interfaces and draws some conclusions in this research area.